Pengaruh Good Corporate Governance (GCG), Stakeholder Pressure, Dan Firm Size Terhadap Kualitas Sustainability Report Pada Perusahaan Sektor Consumer Non-Cyclical Idx-Ic - Wulandari, Septiyana; Amelia, Reva; Afida, Nurhikmatul; Shabihah, Salwa; Rahmatika, Dien Noviany (Universitas Pakuan, 2026)
THE EFFECT OF GOOD CORPORATE GOVERNANCE (GCG), STAKEHOLDER PRESSURE, AND FIRM SIZE ON THE QUALITY OF SUSTAINABILITY REPORTS IN COMPANIES IN THE CONSUMER NON-CYCLICAL SECTOR IDX-IC This study aims to analyze the effect of Good Corporate Governance, Stakeholder Pressure, and Firm Size on the quality of Sustainability Reports in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX). Data was obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the official websites of each company. The research sample consisted of 21 companies. This study used a quantitative approach. This study sought to determine whether good corporate governance, stakeholder pressure, and firm size affect the quality of sustainability reports. Sample collection used purposive sampling techniques. The data analysis method used in this study was Panel Data Regression with data processing analysis using Microsoft Office Software Excel 2021 and eViews 12. The results showed that Good Corporate Governance and Stakeholder Pressure did not affect the quality of Sustainability Reports, while Firm Size had a positive effect on the quality of Sustainability Reports.